Exploring the Niche Concept in a Simple Metaorganism - Deines, Peter; Hammerschmidt, Katrin; Bosch, Thomas C. G. (Frontiers in Microbiology, 2020)
Organisms and their resident microbial communities - the microbiome - form a complex and mostly stable ecosystem. It is known that the composition of the microbiome and bacterial species abundances can have a major impact on host health and Darwinian fitness, but the processes that lead to these microbial patterns have not yet been identified. We here apply the niche concept and trait-based approaches as a first step in understanding the patterns underlying microbial community assembly and structure in the simple metaorganism Hydra. We find that the carrying capacities in single associations do not reflect microbiota densities as part of the community, indicating a discrepancy between the fundamental and realized niche. Whereas in most cases, the realized niche is smaller than the fundamental one, as predicted by theory, the opposite is observed for Hydra’s two main bacterial colonizers. Both, Curvibacter sp. and Duganella sp. benefit from association with the other members of the microbiome and reach higher fractions as compared to when they are the only colonizer. This cannot be linked to any particular trait that is relevant for interacting with the host or by the utilization of specific nutrients but is most likely determined by metabolic interactions between the individual microbiome members.